EVALUASI KINERJA KEUANGAN PADA KOPERASI PEGAWAI NEGERI (KPN) LAJU KECAMATAN MOYO HULU KABUPATEN SUMBAWA - U Usman; Peri Apriliyansah (Pusat Riset dan Publikasi, 2023)
This study aims to examine the financial performance of the Laju Civil Servant Cooperative (KPN), Moyo Hulu District, Sumbawa Regency in 2019-2021. The type of data used is quantitative data in the form of financial performance data obtained from documents or archives of KPN Laju financial reports for 2019-2021. the ratio analysis technique used is in accordance with the Minister of Cooperatives and SMEs of the Republic of Indonesia No. 06 of 2006 concerning guidelines for evaluating cooperatives, namely the liquidity ratio, sovability ratio and profitability/profitability ratio. The results showed that the financial performance of KPN Laju was very poor in terms of liquidity, this can be seen from the current ratio in the